Category of Unlawful Acts That Are Not Corruption Crimes for the Sake of Achieving Legal Certainty - Regi Julian; Rr. Dijan Widijowati; Kristiawanto (International Journal of Science and Society, 2023)
Act of corruption, an act that already exists at an alarming level in Indonesia. The element against the law in corruption cases is essential and determines the existence of a criminal act of corruption that must be accounted for, both positional responsibility and personal responsibility. The consequences of personal responsibility are related to criminal responsibility. This research will be carried out to see how the form of unlawful acts does not meet the elements of corruption and how the concept of legal certainty for unlawful acts does not meet the elements of corruption. This research will be carried out using normative juridical research. This research will then be carried out using the Statute Approach and Case Approach. The results of this study then found at least seven types of formulations in criminal acts of corruption in Law No. 31 of 1999 in conjunction with Law No. 20 of 2001. Suppose an act is considered to have violated the law and can be subject to criminal sanctions. In that case, two elements must be fulfilled: the actus reus (physical element) and mens rea (mental element) elements. The element of actus reus is the essence of the crime itself or the act committed, while the element of mens rea is the inner attitude of the perpetrator at the time of committing the act.